METHODS AND STAGES OF COUNSELING ON YOUTH ENTREPRENEURSHIP (Innovative professional education, 2024)
Creating conditions for supporting youth entrepreneurship involves the organization of counseling for students on youth entrepreneurship in vocational (vocational-technical) education institutions. The relevance of determining the methods and stages of counseling on youth entrepreneurship is due to the fact that this type of psychological support is currently in demand by the readiness of future skilled workers for entrepreneurial activity.
Keywords: vocational education, youth entrepreneurship, skilled worker, counseling methods